Augmented Self‐Association by Electrostatic Forces in Thienopyrrole‐Fused Thiadiazoles that Contain an Ester instead of an Ether Linker. Issue 4 (12th January 2022) - Naito, Yukako; Moriguchi, Ryo; Kitamura, Chitoshi; Matsumoto, Taisuke; Yoshihara, Toshitada; Ishi‐i, Tsutomu; Nagata, Yuka; Takeshita, Hiroki; Yoshizawa, Kazunari; Shiota, Yoshihito; Suzuki, Kazumasa; Kato, Shin‐ichiro
Abstract: During the self‐assembly of π‐conjugated molecules, linkers and substituents can potentially add supportive noncovalent intermolecular interactions to π‐stacking interactions. Here, we report the self‐assembly behavior of thienopyrrole‐fused thiadiazole (TPT) fluorescent dyes that possess ester or ether linkers and dodecyloxy side chains in solution and the condensed phase. A comparison of the self‐association behavior of the ester‐ and ether‐bridged compounds in solution using detailed UV‐vis, fluorescence, and NMR spectroscopic studies revealed that the subtle replacement of the ether linkers by ester linkers leads to a distinct increase in the association constant ( ca . 3–4 fold) and the enthalpic contribution ( ca . 3 kcal mol −1 ). Theoretical calculations suggest that the ester linkers, which are in close proximity to one another due to the π‐stacking interactions, induce attractive electrostatic forces and augment self‐association. The self‐assembly of TPT dyes into well‐defined 1D clusters with high aspect ratios was observed, and their morphologies and crystallinity were investigated using SEM and X‐ray diffraction analyses. TPTs with ester linkers exhibit a columnar liquid crystalline mesophase in the condensed phase. Abstract : Ester linkers enhance self‐association : New fluorescent thienopyrrole‐fused thiadiazoles (TPTs) with either ester or ether bridging groups were synthesized. The subtle replacement of ether linkers by ester linkers leads to a distinct increase ( ca . 3–4 fold) in the association constant and the enthalpic contribution ( ca . 3 kcal mol −1 ). The TPTs having ester linkers produced 1D self‐assembled clusters and formed columnar liquid crystals.